Information Design in effective communications: the Plain Language approach - Mont'Alvão, Claudia (InfoDesign, 2026)
This paper presents and discusses the context of Plain Language and its tight relation with Information Design, as well as the designer’s role in this scenario. To achieve this, definitions of these areas are presented, along with the similarities and differences between Information Design and Ergonomics. Next, the path that led to ISO24495, Plain Language, Part 1, was approved in 2023. From the understanding of the need for an international standard to the importance of conveying information across design process steps, and finally to the translation into Portuguese, a brief glance at this journey is presented. Five parts were proposed, and to fulfill the need of one of them (Part Five: Document design), a pattern library highlighted the role of designers working in this field. Finally, some initiatives in Brazil highlighted and strengthened the designer’s role in advancing citizenship.